Training to Build a Creative and Innovative Young Entrepreneur Mindset - Hanidah, In-In; Halim, Hendra; Fadhil, Rahmat; Kesuma, T. Meldi; Siregar, M. Ridha; Ramadhani, Evi; Ginting, Ledy Mahara; Najla, Najla; Fakhrurrazi, Fakhrurrazi; Rahimi, Sayyid Afdhal El; Zikran, Ghrina (Jurnal Pengabdian Bakti Akademisi, 2024)
The community service activity Training to Build a Creative and Innovative Entrepreneurial Mindset for Young Entrepreneurs aimed to enhance innovation and creativity among beginner entrepreneurs in Banda Aceh. The program involved 100 participants and was conducted using the service learning method, which included practical sessions, group discussions, and business simulations. Pre-test and post-test evaluations showed an average improvement of 40% in understanding innovation concepts, technology adoption, and strategic business planning. Despite challenges such as limited digital infrastructure, the results demonstrated that participants were able to develop innovation-driven business plans. This program contributes to achieving the SDGs, particularly in the areas of decent work and economic growth, as well as industry, innovation, and infrastructure. It is hoped that this activity can serve as a model for future community service programs focused on entrepreneurial development.